2020
DOI: 10.3390/polym12112717
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Microstructure of Polyether Ether Ketone Films Irradiated with 170 keV Protons by Grazing Incidence Small Angle X-ray Scattering (GISAXS) Technology

Abstract: Polyether ether ketone (PEEK) films irradiated with 170 keV protons were calculated by the stopping and ranges of ions in matter (SRIM) software. The results showed that the damage caused by 170 keV protons was only several microns of the PEEK surface, and the ionization absorbed dose and displacement absorbed dose were calculated. The surface morphology and roughness of PEEK after proton irradiation were studied by atomic force microscope (AFM). GISAXS was used to analyze the surface structural information of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…From Figure 7 it can be clearly seen that the melting peak of the pristine PEEK was about 338 °C, while the melting temperature of the irradiated samples except PEEK-7 shifted to a higher temperature range. The thermal stability of the irradiated samples increased during crosslinking due to the stiffening of the polymers [ 26 ]. Figure 8 d shows the maximum weight loss temperature of PEEK samples during the heat flow process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 7 it can be clearly seen that the melting peak of the pristine PEEK was about 338 °C, while the melting temperature of the irradiated samples except PEEK-7 shifted to a higher temperature range. The thermal stability of the irradiated samples increased during crosslinking due to the stiffening of the polymers [ 26 ]. Figure 8 d shows the maximum weight loss temperature of PEEK samples during the heat flow process.…”
Section: Resultsmentioning
confidence: 99%
“…In an electron beam exposed to radiation with a high voltage of 1.5 MeV and a high absorbed dosage of 1000 Mrad, radiation damage to the PEEK matrix was observed [ 25 ]. The effect of irradiation with 170 keV protons on the melting and crystallization temperatures of PEEK was studied by differential scanning calorimetry [ 26 ]. The results of DSC showed that the crystallinity of the polymer after irradiation decreases from 17% to 13%.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, PEEK has been widely used for medical and tissue engineering applications. 26,27 The aromatic backbone structure is responsible for mechanical strength and the pendant ketone group increases the spacing between the molecules, and the ether bond makes the main chain flexible 28 Recently PEEK coatings have demonstrated favorable properties such as reduce stress shielding and can be considered as candidates to improve the performance of existing coatings on biomedical substrates. 29,30 Díez-Pascual reported successful grafting of Carboxylated- PEEK to Zinc Oxide nanoparticles, and hydroxylated- PEEK to the surface of carbon nanotubes to improve the overall performance of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%